Determinants of Smoking Behavior among Migrant Students: A Socio-Ecological Analysis of Spatiotemporal Dynamics in Dormitory Environments - Fransiska Hong; Rosdiana Rosdiana; A. Suyatni Musrah (CV. Social Politic Genius (SIGn), 2025)
Smoking behavior among migrant students represents a complex public health issue that reflects an inconsistency between academic status and lifestyle choices, exacerbated by urban socio-spatial transitional stress. This study aims to contextually analyze the socio-environmental influences on the smoking behavior of migrant students in male dormitories through a multidimensional ecological approach. Employing a qualitative case study design, primary data were gathered through semi-structured in-depth interviews with three informants (comprising one primary informant and two supporting informants), and direct observation on the dormitory front porch, subsequently analyzed using thematic analysis. The findings indicate that smoking initiation is triggered by academic stress associated with the undergraduate thesis as a predisposing factor, reinforced by the transmission of domestic habitus through visual modeling of the actively smoking father as a reinforcing factor, and facilitated by the social territorialization of the dormitory front porch as a permissive smoking zone due to indoor physical restriction policies as an enabling factor. This study concludes that the smoking behavior of migrant students is systemically perpetuated by the conditioning of behavioral architecture and a spatial regulatory vacuum from the regional government of origin as the asset owner. An urgent policy implication is to formulate formal, legally binding Smoke-Free Area (Kawasan Tanpa Rokok/KTR) regulations for official housing contracts and to establish integrated smoking cessation support services within the dormitory.